Recent progress in the characterization of molecular determinants in the Xanthomonas axonopodis pv. manihotis cassava interaction - Verdier, Valerie M.; Restrepo, S.; Mosquera Cifuentes, Gloria Maria; Jorge, V.; López, C.E. (Springer, 2004)
Cassava bacterial blight, caused by Xanthomonas axonopodis pv. manihotis (Xam), is a widespread disease that affects cassava (Manihot esculenta Crantz). Studies on the pathogen population structure, pathogen diagnosis, identification and expression of plant genes involved in resistance have been carried out. Different molecular techniques were developed to assess the genetic diversity among the Xampopulations. Characterization of Xam population dynamics over time had enable us to determine the different factors that are associated with resistance breakdown and those that influence the genetic structure or virulence phenotypes of the pathogen s population. Methods for detecting the pathogen in vegetative planting materials and true seeds were developed and contributed to reduce the impact of the disease. To better understand the genetics of resistance a quantitative trait loci (QTLs) approach was developed. Using a PCR-based strategy with degenerate primers we isolated two resistance gene candidates in cassava. We also characterized a region of a chromosome rich in R-gene like sequence. In this review we also report the main results obtained by transcript profiling methodologies, cDNA-AFLP and ESTs developed by the authors to characterize the genes involved in disease resistance. All together these techniques allowed the identification of molecular markers either associated to CBB resistance or that may represent putative genes involved in disease resistance. This article reviews current knowledge on the molecular cassava Xam interactions.